2022
DOI: 10.3390/ijerph192215070
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of a Diazotrophic Cyanobacterium to Acidification of Paddy Floodwater: N2 Fixation, Photosynthesis, and Oxidative–Antioxidative Characteristics

Abstract: Long-term of excessive fertilization using nitrogen (N) chemical fertilizer caused the acidification of paddy soils. Presently, the impacts of soil acidification on physiological characteristics of diazotrophic cyanobacteria remain unknown. In order to elucidate this issue, the effects of paddy floodwater acidification on activities of respiration, photosynthetic oxygen evolution, and N2 fixation of a paddy diazotrophic cyanobacterium Aliinostoc sp. YYLX235 were investigated in this study. In addition, the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…ROS are byproducts of aerobic metabolism (Sies et al, 2022;Jadhav et al, 2011). Under normal conditions, the production and scavenging of intracellular ROS are in dynamic balance (Yan et al, 2022;Yu et al, 2020). The results presented this study showed that the ROS and the MDA content in GXM increased significantly when the NH + 4 concentration was 67.30 mg L −1 .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…ROS are byproducts of aerobic metabolism (Sies et al, 2022;Jadhav et al, 2011). Under normal conditions, the production and scavenging of intracellular ROS are in dynamic balance (Yan et al, 2022;Yu et al, 2020). The results presented this study showed that the ROS and the MDA content in GXM increased significantly when the NH + 4 concentration was 67.30 mg L −1 .…”
Section: Discussionmentioning
confidence: 66%
“…The paddy soil was collected from the base of Cultivation Garden of Hunan Agricultural University (28 • 18'25" N, 113 • 07'34" E). Simulation of paddy floodwater were prepared according to the methods described by Yan et al (2022). In brief, deionized water (dH 2 O) was mixed with soil in a ratio of 10:9 (W:W), with a flooding depth of 1cm, and incubated at 25 • C under darkness for 15 d. Paddy floodwater was obtained by centrifugation at 12,000 ×g for 10 min.…”
Section: Simulation Of Paddy Floodwatermentioning
confidence: 99%
See 1 more Smart Citation